2000
DOI: 10.1093/hmg/9.9.1303
|View full text |Cite
|
Sign up to set email alerts
|

A novel protein with RNA-binding motifs interacts with ataxin-2

Abstract: Spinocerebellar ataxia type 2 (SCA2) is caused by expansion of a polyglutamine tract in ataxin-2, a protein of unknown function. Using the yeast two-hybrid system, we identified a novel protein, A2BP1 (ataxin-2 binding protein 1) which binds to the C-terminus of ataxin-2. Northern blot analysis showed that A2BP1 was predominantly expressed in muscle and brain. By immunocfluorescent staining, A2BP1 and ataxin-2 were both localized to the trans -Golgi network. Immunocytochemistry showed that A2BP1 was expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
172
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(191 citation statements)
references
References 34 publications
12
172
1
Order By: Relevance
“…Previously, evidence has been provided that human ATXN2 plays a role in RNA-processing pathways (Shibata et al, 2000;Ralser et al, 2005a;Satterfield and Pallanck, 2006). Here, we present further data substantiating that ATXN2 takes part in important steps of mRNA control and regulation.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Previously, evidence has been provided that human ATXN2 plays a role in RNA-processing pathways (Shibata et al, 2000;Ralser et al, 2005a;Satterfield and Pallanck, 2006). Here, we present further data substantiating that ATXN2 takes part in important steps of mRNA control and regulation.…”
Section: Discussionsupporting
confidence: 78%
“…Initially, ATXN2 was identified to interact with the protein A2BP1 (ATXN2 binding protein 1) that contains RNA recognition motifs (Shibata et al, 2000). Along this line, it has been reported that ATXN2 contains an Like Sm (LSm) domain that might be capable of RNA binding as observed for other LSm domain proteins (Neuwald and Koonin, 1998;Achsel et al, 2001;Albrecht et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the only known interacting protein of RBFOX1 was Ataxin-2 (Shibata et al 2000), which is how RBFOX1 was first discovered. We did not find this protein in our analysis, probably because of its tissue-restricted expression.…”
Section: Discussionmentioning
confidence: 99%
“…The PAM2 domain is known to bind RNA. Ataxin‐2 has been observed to interact with A2BP1 (ataxin‐2‐binding protein 1), which might regulate RNA tissue‐specific alternative splicing 23. In addition, ataxin‐2 shows significant homology to the yeast protein Pbp1 (Pab1/PABP‐binding protein 1) that is involved in mRNA polyadenilation.…”
Section: Protein and Its Functionmentioning
confidence: 99%